2014
DOI: 10.3109/09513590.2014.971237
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with menopausal symptoms among middle-aged registered nurses in Beijing

Abstract: Many factors may influence symptoms of the menopause. We found that menopausal status was most strongly associated with most menopausal symptoms, especially hot flashes and sweating. Psychosocial factors also played an important role. A higher frequency of sexual activity negatively correlated with most menopausal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Constipation rates ranged from 20.2% to 28.0%, with 4.3% presenting FI and 7.2%, dual incontinence, while only one study reported the prevalence of POP, finding it to be 16.9% in nurses and midwives . Diagnosed sexual dysfunctions were not found, however, these were associated with other PF subtypes …”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Constipation rates ranged from 20.2% to 28.0%, with 4.3% presenting FI and 7.2%, dual incontinence, while only one study reported the prevalence of POP, finding it to be 16.9% in nurses and midwives . Diagnosed sexual dysfunctions were not found, however, these were associated with other PF subtypes …”
Section: Resultsmentioning
confidence: 94%
“…The mean age of the participants ranged from 21.7 to 48.6 years and the PFD investigated consisted mainly of urinary symptoms ( n = 12). Three studies reported data related to female sexual dysfunctions, three studies reported prevalence of constipation, one investigated faecal and dual incontinence, and one study found a prevalence of POP in female nurses. A total of 13 studies reported data on associated factors and the impact of PFD using validated questionnaires …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations